Knowledge and Attitudes of the Students of Mazandaran University of Medical Sciences Towards COVID-19 in 2020 - Yasaman Shirmohammadi; Fereshte Araghian Mojard; Abolfazl Hossein-Nataj; Hanie Mahmoudpour; Reza Azadi; Tahereh Yaghoubi (Zanjan University of Medical Sciences and Health Services, 2021)
Background: The COVID-19 pandemic has become a great threat to public health and affected the study and lives of undergraduate students in Iran. Objectives: The current study aimed to investigate the knowledge and attitude of students towards COVID-19 at Mazandaran University of Medical Sciences. Methods: This descriptive correlational study was conducted on 151 students of Mazandaran University of Medical Sciences from July 8 to July 14 in 2020. Convenience sampling was conducted based on the census method after completing and signing a consent form. The data were collected using an online questionnaire and analyzed by SPSS 16 software and the statistical tests of Mann-Whitney, Kruskal-Wallis, and Pearson correlation. (P-value≤0.05). Results: The total mean scores of the students' knowledge and attitudes towards COVID-19 were 80.26±5.02 and 16.05±1.65, respectively. A positive and significant relationship was found between the students' total scores of attitude and knowledge towards COVID-19 (r=0.35, P<0.05). The total score of knowledge was significantly associated with the field of study (P=0.004), employment in medical centers (P=0.004), and voluntarily working during the pandemic (P=0.039). Conclusion: The present findings indicated that the students were equipped with the right knowledge and attitude towards the COVID-19 pandemic. Since this disease is new, and authentic academic centers come up with daily updates on relevant information about the prevention, treatment, symptoms, and transmission of the disease, health policymakers and the directors of training centers are recommended to make continuous efforts to promote and upgrade medical sciences students' information about the disease.